ANALISIS PENGARUH PENDAPATAN PEKERJA WANITA TERHADAP PENDAPATAN KELUAGA (STUDI KASUS PEKERJA WANITA PENYAPU JALAN DI KOTA PALEMBANG) - Leo Budiriansyah; Hisbullah Basri (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
ABSTRACT This study aims to determine the effect of income of female street sweeper workers on the welfare of their families. The research case study is street sweeper female workers in Palembang City. This study uses primary data through the method of collecting data using questionnaires, interviews and literature studies. The analysis technique used is multiple regression analysis using three regression models. The results showed that the Female Street Sweeper Income Ratio of Family Income had a significant and opposite effect on Family Income while the Variable Numbers of Family Members also had a significant but unidirectional effect on Total Family Income. More family members will increase total income. The regression results also show that the role of female street sweepers is quite important in generating additional income in the family so that it can support the amount of consumption needed by the family. The greater number of family members will make the consumption value increase. The number of family members also has a significant effect on the ratio of debt to family income. More and more family members will make consumption increase so that the burden of needs can cause debt to increase. Whereas female road sweeper income also has a significant effect but the direction is opposite to the family debt ratio. This means that the greater the income of road sweepers will reduce the high ratio of family debt to total family income Keywords: Road Sweeper Women Workers, Income, Family Welfare